Islamic Religious Education Learning Management Based on Mosques at Patani Islamic Senior High School, Mappakasunggu District, Takalar Regency - Sumarni, Sumarni (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to find out how the Management of Mosque-Based Islamic Education Learning at Patani Islamic High School. This research is a qualitative research which when viewed based on its place is field research. The sources of data in this study are teachers and students. Data collection is carried out by observation, interviews and documentation methods, to analyze data using a qualitative descriptive approach. This study shows: 1) Management of PAI learning in SMA Islam Patani Mappapasunggu District, Takalar Regency, namely through planning, organizing, and evaluating. 2) Implementation of mosque-based learning programs at Patani Islamic High School, Mappakasunggu District, Takalar Regency, namely through Habituation of Noble Morals, Tuntuas Read and write the Qur'an, Da'wah Formation, Dhuhr prayer in congregation. 3) Supporting factors are full support from the principal, awareness from students, and support from parents and the student environment. While the inhibiting factors are the quality of teachers who are less creative as teachers of Islamic religious education, the enthusiasm for student learning is less conducive